STUDY OF ANTI-BACTERIAL AND ANTI-INFLAMMATORY PROPERTIES OF INDONESIA’S FLORA BIODIVERSITY AS DRUG CANDIDATES FOR DIABETIC ULCER THROUGH IN SILICO AND IN VITRO APPROACH - Tiffanny, Cecilia; Regina, Aurelia; Chen, Davin Handreas; Rosyati, Margaretha Maria (BRIN - Badan Riset dan Inovasi Nasional, 2024)
This study is driven by the substantial increase in the number of diabetes mellitus patients, which is projected to triple by 2030 and the immense potential of Indonesia's extensive biodiversity. Diabetic ulcers represent one of the most common complications stemming from uncontrolled diabetes mellitus. Therefore, this research aims to determine the therapeutic potential of Indonesian biodiversity for diabetic ulcers, focusing on the anti-bacterial and anti-inflammatory properties of secondary metabolite derivatives, employing both in silico and in vitro approaches. Initially, the research employed an in silico approach, conducting molecular docking and molecular dynamics simulations on reference ligands obtained from the 6KVS receptor for Staphylococcus aureus bacteria and the 5KIR for the COX-2 protein. Molecular docking was performed for 18 secondary metabolite derivative test compounds using Autodock Vina, followed by molecular dynamics simulations. The results of the molecular dynamics simulations showed that flavanonols exhibited the highest stability among the test compounds, with an average root mean squared deviation of 0.139493 Å for anti-bacterial tests and 0.182499 Å for anti-inflammatory tests after 50 ns simulation. Based on the results of molecular dynamics simulations, in vitro anti-bacterial and anti-inflammatory testing was conducted using flavanonol compounds found in Ananas comosus plants. In the anti-bacterial test, the pineapple extract, at a 5% concentration, exhibited the largest inhibitory zone diameter, 3.53 mm. In the anti-inflammatory tests, the pineapple extract at an optimal concentration of 600 ppm showed the highest absorbance value for protein denaturation, measuring 0.11133 au.